Politik Etnisitas dalam Pemekaran Daerah - Fikarwin Zuska (Antropologi Indonesia, 2012)
This paper deals with the regional partition which do not always take place due to the considerations as commonly stated in official explanations, and also it does not like the outcome of the scientific analysis on the interests of local elites in efforts to devide regions for seizing local power in the new regions. In addition, this paper also shows that ethnic politics is often interwined with the region partitions. The local elite politically quite often to put forward ethnicity and identity loyalties as a political resources for demanding the regional division. Ethnic identity and the usage of collective ethnic identity as a never lasting prime mover. These can be politically seen from ethnic Pakpak behaviors in encountering ethnic Batak Toba in their own territory regarding the establishment of Great Pakpak province. Key-words: Pakpak, politics of ethnicity, ethnic identity, regional partition